Improving blood safety and availability: a collective mindfulness perspective in the supply chain - Lusiantoro, Luluk; Yates, Nicola (Emerald, 2021)
Purpose – Maintaining a safe and available supply of blood requires a mindfully coordinated supply chain (SC) and is fundamental to the effective operation of health systems across the world. This study investigates how blood supply chain (BSC) actors demonstrate collective mindfulness (CM) principles in their operations and how these demonstrations lead to improvements in blood safety and availability (BSA) in different operational contexts. Design/methodology/approach – Six case studies drawn from two contrasting BSCs, the UK and Indonesia, which differ in structure and regulation are investigated in this research. Qualitative data are collected and analysed using template analysis. Findings – The cases reveal how the CM principles are demonstrated in the supply chain context in a range of operational conditions and their impact on BSA. The BSC actors in the more centralised and tightly regulated cases display more behaviours consistent with more of the CM principles over a greater range of operational conditions compared to those in the more decentralised and loosely regulated cases. As such, more improvements in BSA are found in the former compared to the latter cases. Originality/value – This paper is considered the first to investigate the demonstration of CM principles at the SC as opposed to the single organisational level. It proposes an alternative approach to understanding and evaluating reliability performance using behavioural rather than statistical principles.
Keywords: Blood; Safety and availability; System reliability; Collective mindfulness; Theory elaboration; Template analysis